Severe Deoxyguanosine Kinase Deficiency in Austria: A 6-Patient Series. Issue 1 (January 2019) - Waich, Stephanie; Roscher, Anne; Brunner-Krainz, Michaela; Cortina, Gerard; Köstl, Gerhard; Feichtinger, Rene G.; Entenmann, Andreas; Müller, Thomas; Knisely, A.S.; Mayr, Johannes A.; Janecke, Andreas R.; Vodopiutz, Julia
Abstract : ABSTRACT: Mutations in the nuclear gene DGUOK, encoding deoxyguanosine kinase, cause an infantile hepatocerebral type of mitochondrial depletion syndrome (MDS). We report 6 MDS patients harboring bi-allelic DGUOK mutations, of which 3 are novel, including a large intragenic Austrian founder deletion. One patient was diagnosed with hepatocellular carcinoma aged 6 months, supporting a link between mitochondrial DNA depletion and tumorigenesis; liver transplantation proved beneficial with regard to both tumor treatment and psychomotor development.